Identification of IQGAP1 as a SLC26A4 (Pendrin)-Binding Protein in the Kidney - Xu, Jie; Barone, Sharon; Varasteh Kia, Mujan; Holliday, L. Shannon; Zahedi, Kamyar; Soleimani, Manoocher (Frontiers in Molecular Biosciences, 2022)
Background: Several members of the SLC26A family of transporters, including SLC26A3 (DRA), SLC26A5 (prestin), SLC26A6 (PAT-1; CFEX) and SLC26A9, form multi-protein complexes with a number of molecules (e.g., cytoskeletal proteins, anchor-ing or adaptor proteins, cystic fibrosis transmembrane conductance regulator, and protein kinases). These interactions provide regulatory signals for these molecules. However, the identity of proteins that interact with the Cl-/HCO3- exchanger, SLC26A4 (pendrin), have yet to be determined. The purpose of this study is to identify the protein(s) that interact with pendrin. Methods: A yeast two hybrid (Y2H) system was employed to screen a mouse kidney cDNA library using the C-terminal fragment of SLC26A4 as bait. Immunofluorescence microscopic examination of kidney sections, as well as co-immunoprecipitation assays, were performed using affinity purified antibodies and kidney protein extracts to confirm the co-localization and interaction of pendrin and the identified binding partners. Co-expression studies were carried out in cultured cells to examine the effect of binding partners on pendrin trafficking and activity. Results: The Y2H studies identified IQGAP-1 as a protein that binds to SLC26A4’s c-terminus. Co-immunoprecipitation experiments using affinity purified anti-IQGAP-1 antibodies followed by western blot analysis of kidney protein eluates using pendrin-specific antibodies confirmed the interaction of pendrin and IQGAP-1. Immunofluorescence microscopy studies demonstrated that IQGAP-1 co-localizes with pendrin on the apical membrane of B-intercalated cells, whereas it shows basolateral expression in A-intercalated cells in the cortical collecting duct (CCD). Functional and confocal studies in HEK-293 cells demonstrated that the co-transfection of pendrin and IQGAP-1 shows strong co-localization of the two molecules along with enhanced Cl-/HCO3- exchanger activity. Conclusions: IQGAP-1 was identified as proteins that bind to the C-terminus of pendrin in B-intercalated cells. IQGAP-1 co-localized with pendrin on the apical membrane of B-intercalated cells. Co-expression with IQGAP-1 with pendrin resulted in strong co-localization of the two molecules and increased the activity of pendrin in plasma mem-brane in cultured cells. We propose that pendrin’s interaction with IQGAP-1 may play a critical role in the regulation of CCD function and physiology, and that disruption of this interaction could contribute to altered pendrin trafficking and/or activity in pathophysiologic states.